Respuesta :

Answer:

4092

Step-by-step explanation:

r = 2

a1 = 4×(2)^(1 - 1) = 4

S10 = a1×((1 - r^10)/(1 - r)

= 4×((1 - 2^10)/(1 - 2))

= 4×((1 - 2^10)/-1)

= 4×(-(1 - 2^10))

= -4×(1 - 2^10)

= -4 + 4 × 2^10

= -4 + 2^2 × 2^10

= -4 + 2^12

= -4 + 4096

= 4092

Answer:

  • 4092

Step-by-step explanation:

Given is a GP with:

  • Common ratio r = 2
  • First term a = 4*2¹⁻¹ = 4*1 = 4

We need to find the sum of the first 10 terms:

  • Sₙ = a(rⁿ - 1)/(r - 1)
  • S₁₀ = 4*(2¹⁰ - 1)/(2 - 1) = 4*(1024 - 1)/1 = 4(1023) = 4092
ACCESS MORE